Doses e parcelamento da adubação potássica na cultura da batata (Solanum tuberosum L.) - Job, André Luiz Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
With the use of more productive potato (Solanum tuberosum L.) cultivars, the plant’s demand for nutrients has possibly increased, raising the necessity of adjustments on fertilizer application. Potassium (K), which is extracted in high amounts, is one of the main nutrients absorbed by the plant. This compound is of pivotal importance to potato development, especially to increase its yield and to generate high quality tubers. Many producers are making use of fertilization without a proper technical recommendation. As K uptake by the plant is very high, low K rates and inadequate management can impair tuber yield, mainly in soil with low K availability. In this context, this study aimed to evaluate the effects of K fertilization rates and split application on nutrition and yield or potato crop, cv. Agata. For this, three field experiments was carried out on clay-textured soils with low (0.7 mmolc dm-3), medium (1.6 mmolc dm-3) and high (3.7 mmolc dm-3) exchangeable K concentration. These experiments was conducted under a randomized block design using a 3x2+1 factorial scheme, with four replications. The treatments consisted of three K rates (100, 200, and 400 kg ha-1 K2O), combined with two forms of split application (100 % at planting furrow or 50% at planting furrow + 50% at sidedressing, during hilling) and a control (without K application). Regardless of installments, increasing K rates showed an increase in K concentration in leaf of potato grown in soils with low, medium, and high K availability, but more markedly in soil with low availability. In soil with low concentration of exchangeable K, the application of K rate totally at planting furrow increased the concentration of K in the leaf than when split applied at planting and hilling. Regardless of the soil K availability, K fertilization reduced the concentrations of P, Ca, and Mg in leaf of potato crop and little influenced the ...

Com o uso de cultivares de batata (Solanum tuberosum L.) mais produtivas, possivelmente a demanda por nutrientes também ficou maior, levando a necessidade de se adequar a adubação. Dentre os nutrientes absorvidos pela cultura, destaca-se o potássio (K), que é extraído em grande quantidade, e é de extrema importância para o desenvolvimento da cultura, para a elevação da produtividade e para proporcionar tubérculos de maior qualidade. Muitos produtores estão adotando adubações sem recomendação técnicas e, como o K é muito extraído pela cultura, as baixas doses de K e manejo inadequado podem estar limitando a produtividade, principalmente em áreas com baixos teores de K disponível. Diante do exposto, o objetivo deste trabalho foi avaliar o efeito de doses e do parcelamento da adubação potássica na nutrição e produtividade da cultura da batata, cv. Ágata. Foram realizados três experimentos em campo, em solos de textura argilosa e com teores baixo (0,7 mmolc dm-3), médio (1,6 mmolc dm-3) e alto (3,7 mmolc dm-3) de K trocável. Os experimentos foram conduzidos no delineamento experimental de blocos casualizados, em esquema fatorial 3x2+1, com quatro repetições. Os tratamentos foram compostos pela combinação de três doses de K (100, 200 e 400 kg ha-1 de K2O), com duas formas de parcelamento (100% no sulco de plantio e 50% no sulco + 50% em cobertura, por ocasião da amontoa) e mais uma testemunha (sem aplicação de K). Independentemente do parcelamento, o aumento das doses de K proporcionou incremento no teor de K na folha da batateira, cultivada em solos com baixa, média e alta disponibilidade de K, porém, de forma mais acentuada no solo com baixo teor. No solo com baixo teor de K trocável, a aplicação da dose K totalmente no sulco de plantio proporcionou maior teor de K na folha do que quando parcelado no plantio e em cobertura. Independentemente da disponibilidade de ...
Keywords: Batata - Cultivo; Adubação; Potassio na agricultura; Potassium in agriculture